ANALISIS PENGARUH HARGA, NILAI TUKAR RUPIAH DAN PRODUKSI TERHADAP VOLUME EKSPOR KOPI INDONESIA - Putu Rama Yudhi Pratama; Made Kembar Sri Budhi (Universitas Udayana, 2023)
The high export of coffee commodities from Indonesia has made a major contribution to the world as a coffee supplier. This study aims to analyze the effect of coffee prices, the rupiah exchange rate and production have a simultaneous effect on Indonesia's coffee exports during 2001-2020. To analyze the effect of coffee prices, the rupiah exchange rate and production partially on Indonesian coffee exports during 2001-2020. The number of samples is 20 observations. The data collection method used in this study is to use non-behavior observation methods. The data analysis technique used is multiple linear regression analysis. The results of the study found that prices, exchange rates and production simultaneously had a significant effect on coffee exports in Indonesia. Price, rupiah exchange rate and production have a positive and significant effect on coffee exports in Indonesia. The variable that has the dominant influence on coffee exports in Indonesia is price.